The Quantitative Characteristics of Cross-Bred Native Chicken (Sentul X Arab Chicken and Merawang X Arab Chicken) - Irmaya. H, Dika; Suyadi, Suyadi; Depison, Depison; Ardiantoro, Ari (Buletin Peternakan, 2024)
The research aims to analyze the production potential and opportunities to increase the productivity of each cross-bred animal based on its quantitative characteristics. The livestock material used in this research was 50 Sera chickens (Sentul chickens x Arabian chickens) and 50 Mera chickens (Merawang chickens x Arabian chickens). The research was carried out by raising chickens from DOC to 3 months of age. The quantitative data involve body weight, weight gain, and body measurements (Head Length, Head Circumference, Head Height, Neck Length, Neck Circumference, Wing Length, Back Length, Back Height, Chest Length, Chest Width, Shank Length, Shank Circumference, Length Third Finger and Pubic Bone Distance). The quantitative data that has been observed is then analyzed through the t-test. Then, PCA is used to identify body shape and size determinants in Sera and Mera chickens. Statistical analysis was carried out using Minitab software version 21. The results obtained showed that the body weights of Sera and Mera chickens were significantly different (p<0.05) from DOC to 3 months of age. A significant increase in productivity in crosses between Sentul chickens and Arabian chickens and Merawang chickens with Arabian chickens occurs starting at 1-2 months. Sera and Mera chickens' body sizes differed significantly (p<0.05). The total diversity of PC1 in Sera chickens was 79.8%, and in Mera chickens, it was 70.6%. Meanwhile, the total PC2 diversity of Sera chickens was 17.7%, and Mera chickens were 7.9%. In conclusion, Sera chickens have the highest quantitative characteristics compared to Mera chickens, and the highest body weight gain occurs at 1-2 months in both Sera and Mera chickens.  Based on principal component analysis. The body size characteristic of Sera chickens is shank length, while in Mera chickens, it is chest length. The distinct shape of Sera chickens is body height, while in Mera chickens, it is shank length.